Effectiveness of planned teaching programme on knowledge regarding Prevention of Nosocomial Infection - Sharma, Atul; Bhattacharya, Chanu (Indian Journal of Nursing Sciences, 2024)
Aim: A study to assess the effectiveness of planned teaching programmers (PTP) on knowledge regarding prevention of nosocomial infection. The objectives of the study were to 1. Assess the knowledge of Final year B.Sc. Nursing students regarding prevention of nosocomial infection. 2. Find the effectiveness of planned teaching programme on the prevention of nosocomial infections. Materials and methods: An evaluator approach was used for this study, which was carried out among Final year B.Sc. Nursing students in Sahyadri College of Nursing, Mangalore. 50 samples were selected using purposive sampling technique. Data was collected by administering a structured knowledge questionnaire to assess their knowledge. Investigators using audiovisual aids gave a planned teaching programme. Data analyses were done by using descriptive statistics, such as frequency, percentage, mean and standard deviation. Result: The mean pre-test score was 13.8 whereas the post-test score was 23. This shows that the planned teaching programme on the prevention of nosocomial infection was effective in increasing the knowledge of the students. Conclusion: The mean pre-test score was 13.8 whereas the mean post-test score was 23. The above facts prompt us to conclude that the planned teaching programme is an effective method to increase the knowledge regarding the prevention of nosocomial infections.